Influences of particle content, size and particle/matrix bonding strength on the gas transmission coefficient of carbon fiber reinforced epoxy. (10th November 2021) - Yuan, Yuhuan; Peng, Cong; Sun, Tao; Chen, Duo; Gao, Chang; Li, Shichao; Wu, Zhanjun
Abstract: Carbon fiber reinforced epoxy (CFRE) composites have great advantages in manufacturing cryogenic propellant tanks of launch vehicle. However, due to the great difference in thermal expansion coefficient (CTE) between the matrix and carbon fiber, damage will be generated in the CFRE when the temperature changes dramatically. As a result, there is potential risk of leakage of the propellant. Silica particles of different conditions were prepared and used as fillers for the epoxy matrix. The effects of content, size, KH560 grafting rate of the particles and their interactions on CTE, tensile strength of the matrix and gas transmission coefficient (GTC) of the CFRE at 77 K were studied using Taguchi method of two levels. The influence mechanism was studied through short-beam strength test and the morphology analysis of the fractured specimens. The results show that the content of particles is the most influential factor on CTE of the matrix and the GTC of the CFRE (with contribution of 56.4%). Small particle size shows superiority on reducing CTE and GTC at low particle content. However, this superiority disappeared when the content increases to 30 wt %. High KH560 grafting rate was beneficial to reducing CTE and GTC, especially for large particles. The validity of the obtained regression equation was confirmed and it was proved to be effective in predicting and optimizing the impermeability of the material. Graphical abstract: Image 1 Highlights: Taguchi method was used to quantitatively analyze the effects of silica particles on the impermeability of the CFRE. The particle size and KH560 grafting ratio was controlled by varying the reaction conditions. The regression equation of gas transmission coefficient (GTC) was formulated and proved valid on estimating GTC of the CFRE.